ANALISIS SIFAT MACHIAVELLIAN DAN PEMBELAJARAN ETIKA TERHADAP SIKAP ETIS AKUNTAN DAN MAHASISWA AKUNTANSI - Widyaningrum, Triyana -; Sarwono, Aris Eddy (Universitas Slamet Riyadi, 2012)
ABSTRACT The banking sector has a role in intermediating the relationship with the debtor. Some of that can be done to improve the role of banks in the development of small micro environmentally sound. Provisions for small-micro businesses require to make document management environment to date has not been set. There are provisions for medium and large scale businesses. Banking policy on environmental aspects in order to loan disbursement for the business or industry is still valid only for large and medium scale enterprises. For it is necessary to study how banks can establish policies to ensure the debtor to manage natural resources and the environment well, especially for small businesses Micro. Â Keywords: Machiavellian, Ethics, Ethical Attitudes, Erating A, Dan Erating B.